Impact of three rounds of mass preventive chemotherapy on prevalence and intensities of Schistosoma mansoni infection among an adult population on Ukerewe Island, north-western Tanzania - Chiombola, Crecencia E.; Mwangoka, Erick Simon; Baumba, Tumaini; Mkombe, Charles Guya; Kreibich, Saskia; Kasang, Christa; Fuss, Antje; Mueller, Andreas; Sabuni, Paul Alikado; Mazigo, Humphrey D. (Frontiers in Tropical Diseases, 2025)
BackgroundThe World Health Organization has called for the elimination of schistosomiasis as a public health problem by 2030 through expanding praziquantel delivery to all community members, specifically targeting the foci of the disease. The current project is responding to this call by implementing community-based mass preventive chemotherapy (PC) to an at-risk adult population on Ukerewe Island, northwestern Tanzania. To date, three rounds of mass preventive chemotherapy have been implemented and here we report the effect of these treatment rounds on the prevalence and intensity of S. mansoni infection. Secondarily, we report on the treatment coverage in all the treatment rounds.MethodsA community-based cross-sectional study was conducted in 20 villages and included randomly selected adults aged ≥15 years. A single stool sample was obtained from each consenting participant and examined for S. mansoni infection using the Kato Katz technique. A questionnaire was used to collect the demographic information of the participants. The World Health Organization’s community evaluation survey (CES) methods were adapted to assess treatment coverage. Two weeks after each treatment round (In June 2021, January 2023, and June 2023), CESs were conducted among adults from randomly selected households.ResultsFor parasitological surveys, a total of 2,041 participants (47.8% men and 52.2% women) were involved. After three rounds of treatment, the overall adjusted prevalence of S. mansoni infection was 9.5% (95%CI:8.3-10.8) and the geometrical mean egg intensity of infection was 79.9 eggs per gram (epg) of feces (95% CI:71.2-89.8). The prevalence declined by 68.8% (from 30.4% to 9.5%, P<0.0001) and intensity of infection declined by 24.1% (from 105.3 epg at baseline to 79.9 epg, P<0.0001). After three rounds of mass PC, the proportion of heavily infected adult individuals significantly declined by 81% (from 13.7% at baseline to 2.6%). For the coverage survey, a total of 12,531 adult individuals were interviewed after each round of treatment. Coverages of 80.8%, 78.5%, and 81.9% were recorded for treatment rounds one, two, and three, respectively.ConclusionOverall, the three rounds of mass preventive chemotherapy led to declines in the prevalence and intensity of S. mansoni infection in the targeted population. In all the targeted villages, the treatment coverage of praziquantel was above the recommended threshold of ≥ 75%, but improvement is needed to achieve higher coverage in the coming treatment rounds, which in turn will have a high impact on the disease prevalence. In addition, to achieve the elimination stage, the targeted villages still need additional treatment rounds which should be supported with other complementary interventions such as improved water supply, sanitation, and hygiene.